Nephrology Social Workers' Caseloads and Hourly Wages in 2014 and 2017: Findings from the National Kidney Foundation Council of Nephrology Social Workers Professional Practice Survey - Merighi, PhD, MSW, LISW, Joseph; Zheng, MSW, Mingyang; Browne, PhD, MSW, NSW-C, Teri (The Journal of Nephrology Social Work, 2018)
In 2014 and 2017, the National Kidney Foundation Council of Nephrology Social Workers (NKF-CNSW) conducted online surveys of nephrology social workers employed in outpatient dialysis settings and transplant programs to assess caseload and salary trends at the state, national, and End-Stage Renal Disease Network levels. Between 2014 and 2017, the mean caseloads for outpatient dialysis social workers remained steady at 75 for those employed 20–31 hrs/wk, increased from 113.2 to 126.9 (up 12.1%) for those employed 32–40 hrs/wk, and increased from 116.1 to 129.5 (up 11.5%) for those employed 40 hrs/wk. Median caseloads showed a similar pattern between 2014 and 2017 for those employed 32–40 hrs/wk (110.0 to 120.0; up 9.1%) and for those employed 40 hrs/week (117.0 to 120.0; up 2.6%). Increases in mean hourly wage between 2014 and 2017 were also reported across all three employment status groups: $29.45 to $31.31 per hour (up 6.3%) for those working 20–31 hrs/wk, $28.23 to $30.62 per hour (up 8.5%) for those working 32–40 hrs/wk, and $28.21 to $30.48 per hour (up 8.0%) for dialysis social workers employed 40 hrs/wk. Annual pre-transplant evaluations of potential donors increased between 2014 and 2017 for transplant social workers who were employed full time (32–40 hrs/wk) and those who worked 40 hrs/wk. Specifically, the mean number of potential donor evaluations increased from 22.1 to 33.8 (up 52.9%) for those employed 32–40 hrs/wk and 23.0 to 33.8 (up 46.9%) for those employed 40 hrs/wk. Pre-transplant evaluations of potential recipients decreased for those employed full-time (283.7 to 219.2, down 22.7%) and for those employed 40 hrs/wk (315.6 to 219.2, down 30.5%). Mean hourly wage data showed an increase for transplant social workers employed full time ($30.74 to $31.50, up 2.5%) and for those employed 40 hrs/wk ($28.74 to $31.03, up 7.9%). In general, increases in social work caseloads and increases in hourly wages were found on a national level; however, variability in mean caseloads and mean hourly wages across ESRD Networks and states persists.